2018
DOI: 10.1140/epjst/e2018-800035-y
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of solitary state appearance in an ensemble of nonlocally coupled Lozi maps

Abstract: We study the peculiarities of the solitary state appearance in the ensemble of nonlocally coupled chaotic maps. We show that nonlocal coupling and features of the partial elements lead to arising of multistability in the system. The existence of solitary state is caused by formation of two attractive sets with different basins of attraction. Their basins are analysed depending on coupling parameters.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…We cannot designate the chimera patterns as strong chimera (Zhang and Motter, 2021). However, some recent reports consider this latter chimera pattern as a solitary state (Jaros et al, 2018;Semenova et al, 2018;Rybalova et al, 2021) since a single oscillator behaves differently, in the dynamical sense, from the other two coherent oscillators.…”
Section: Discussionmentioning
confidence: 97%
“…We cannot designate the chimera patterns as strong chimera (Zhang and Motter, 2021). However, some recent reports consider this latter chimera pattern as a solitary state (Jaros et al, 2018;Semenova et al, 2018;Rybalova et al, 2021) since a single oscillator behaves differently, in the dynamical sense, from the other two coherent oscillators.…”
Section: Discussionmentioning
confidence: 97%
“…During the transition, more and more solitary oscillators appear, growing almost linearly with the decrease in the coupling strength. This is the result of an increase of the size of the basin of attraction of the solitary set with a decrease in the coupling, as more random initial conditions lie in this basin [52]. To also induce solitary states in maps with nonhyperbolic attractors, a multiplicative noise can be added to the coupling constant, thus also showing the existence of the solitary state in a noisy system [53].…”
Section: Weakly Coupled Oscillators-kuramoto Modelmentioning
confidence: 99%
“…The surprising aspect of this phenomenon is that these states were detected in systems of identical oscillators coupled in a symmetric ring topology with a symmetric interaction function, and they coexist with a stable completely synchronized state. The last a) Electronic mail: zergon@gmx.net decade has seen an increasing interest in phase and amplitude chimeras both in time-continuous systems [14][15][16][17][18][19][20][21][22] and in timediscrete maps [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] . It has been shown that they are not limited to phase oscillators, but can be found for a large variety of different dynamics including neural systems [42][43][44][45][46][47][48] .…”
Section: Introductionmentioning
confidence: 99%